FEATURES OF OUTPUT EVALUATION FOR PUBLIC SECTOR OF THE ECONOMY - A. Abroskin (Publishing House of the State University of Management, 2017)
The article is dedicated to topical issues of strategic planning and public sector management information base expansion on the basis of organizations’ financial statements data using. The article covers the problems of output evaluation for public sector of the economy organizations, represented by government corporations and general government units; in the article are also proposed general schemes of output calculation for government non-financial and financial corporations.